2014
DOI: 10.11648/j.ijnfs.20140302.26
|View full text |Cite
|
Sign up to set email alerts
|

UV-Spectrophotometry Determination of Taurine in Energy Drink Mixtures

Abstract: Abstract:The aim of this study is developing and validation of UV-spectrophotometric method for determination of taurine in energy drink mixtures. The investigation includes validation of procedures for performance of the tests for identification, purity and assay. Analytical parameters precision, accuracy, selectivity, linearity, limit of detection and limit of quantitation were studied and compared. Developed method allows selectively determination of taurine in the present of caffeine at different condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is conjugated in the liver with chenodeoxycholic acid and cholic acid and form the bile salts sodium taurochenodeoxycholate and sodium taurocholate [34]. Taurine is involved in the formation of the surface-active substances, which promote the emulsification of the fatty acids in the diet [14].…”
Section: Pharmacological Effects Of Taurinementioning
confidence: 99%
“…It is conjugated in the liver with chenodeoxycholic acid and cholic acid and form the bile salts sodium taurochenodeoxycholate and sodium taurocholate [34]. Taurine is involved in the formation of the surface-active substances, which promote the emulsification of the fatty acids in the diet [14].…”
Section: Pharmacological Effects Of Taurinementioning
confidence: 99%
“…It has physiological effects and pharmacological actions such as a neurotransmitter, antioxidant, modulator of intracellular calcium levels, osmolyte, protect the liver and benefit the gallbladder [5]. The various physiological functions of taurine are explained with amino terminal group in the structure and sulfonic acid group moiety [6]. It is added to energy drinks maybe due to its purposed stimulant effects and it may improve athletic performance, improve attention and verbal reasoning skills [7,4].…”
Section: Introductionmentioning
confidence: 99%
“…Taurine has several essential physiological functions such as; anti-inflammatory properties, formation of bile salts, acts as an antioxidant, membrane stabilization, and osmosis, liver detoxication by binding harmful substances, protection against glutamate cytotoxicity, neurotransmitter and a modulator of intracellular ions levels [8,9]. Studies have shown that high concentration of taurine can induce side effects such as; declining heart rates while arterial blood pressure is increased (with caffeine), hypoglycemia, dizziness, diarrhea, peptic ulcer, influence defects in nerve blood flow and dehydration [6,10]. The combination of taurine with caffeine, amino acids and guarana in energy drinks increases the risk of side effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…HPLC with electrochemical, refractive index detection and mass spectrometry [7,11] were also reported. Methods using techniques such as capillary electrophoresis [12], nuclear magnetic resonance spectroscopy (H1-NMR) [13] , UVspectrophotometric methods [10,14] and spectrofluorimetric [15] were also found in the literature. However, most of these methods have drawbacks, such as they require expensive equipment and derivatizing reagent [7,9] or have low sensitivity [12,14].…”
Section: Introductionmentioning
confidence: 99%